The fall of five - Lore, Pittacus (Harper, 2013)
The Garde is hopelessly outmatched by the annihilating Mogadorian ruler and draws unexpectedly close to finding the last remaining member of their group of alien survivors.
After facing off with the Mogadorian ruler and almost being annihilated, the Garde go into hiding. They must learn to master their Legacies and learn to work together as a team. When they receive a sign from Number Five -- a crop circle in the shape of a Loric symbol -- they know they are close to being reunited. But could it be a trap? Time is running out, and the only thing they know for certain is that they have to get to Five before it's too late.
HL 740
Keywords: Extraterrestrial beings -- Fiction; Extraterrestrial beings -- Juvenile fiction; Science fiction